PENGARUH PENAMBAHAN AGAR-AGAR, ALGINAT DAN KERAGINAN TERHADAP DAYA SIMPAN DAN DAYA TERIMA ORGANOLEPTIK SUSU TEMPE - Yuliantini, Emy (JURNAL MEDIA KESEHATAN, 2012)
Tempe is the ancestral heritage of Indonesia are priceless. Unfortunately, it turns up the current status of soybean as part of the diet of Indonesian society has not appreciated as it should be. For those who like tempeh, tempeh consumed more because it's cheap. As for those who do not like, tempeh regarded as second-class food. Development of tempeh can be established range of food varied and creative, one soybean milk. But tempeh has a weakness, a bitter taste and sediment. Thus a processing technique that can reduce the weaknesses. One was the addition of gelatin as an emulsifier. Research Methods. This study is an experimental research by providing treatment in a sample of the addition of agar-agar, alginate, carrageenan on milk and tempe. The study was conducted with a completely randomized design (CRD). Further analysis of the obtained blue methilen statistically analyzed by One-Way ANOVA test with a significance level of 5% Two Way Anova test followed. As for the sensory data using a test like or Hedonic scale Scale Test with 30 panelists, and the data obtained is processed by Kruskal Wallis test with subsequent Mann Whitney test. Research. Results showed no effect of the addition of agar-agar, alginate and carrageenan to changes in methylene blue milk tempeh. In general, the organoleptic properties of soybean milk is the preferred milk with the addition of soybean agar instant. This study can be continued by looking at the effect of adding flavor to the milk's favorite tempe.